Meningkatkan Pengetahuan Ibu mengenai Gizi Seimbang untuk Balita: Pengalaman Pengabdian Masyarakat di Kabupaten Minahasa Utara: Increased Maternal Knowledge on Balanced Nutrition for Toddlers: A Community Service Experience in North Minahasa Regency - Yulianty Sanggelorang; Kaisar Rompas; Lafita Gobel; Valenia Kereh; Marcella Manoppo; Christa Bidara; Jelsy Anggela; Avelina da Gomez; Regina Manangkot; Sefanya Katanga (Vivabio: Jurnal Pengabdian Multidisiplin, 2023)
The nutritional issues in Indonesia remain a significant concern, particularly in the context of child nutrition, which can serve as an obstruction to their physical and cognitive development. Nutritional problems are attributed to various factors, with maternal knowledge of nutrition being one of the diverse determinants. The objective of this community service activity is to enhance maternal knowledge to proactively address nutritional challenges in toddlers, drawing upon the principles of a balanced nutritional guideline. The implementation method of this activity is through health counselling held at the Wineru Village Head’s Office in North Minahasa Regency on July 28, 2023. This health counselling session is specifically targeted at mothers with toddlers, as, in general, this demographic represents a key group for childcare in Indonesia. The assessment of maternal knowledge concludes with the distribution of supplementary feeding in the form of biscuits and milk to all attending participants. Data analysis using a paired t-test indicates a significant difference in the average scores before and after the counselling session (p-value <0.05). Therefore, it can be concluded that this counseling activity has been successful in effectively enhancing knowledge, and it is hoped that this increased awareness will be applied by participants in their daily practices.   ABSTRAK Permasalahan gizi di Indonesia masih menjadi isu yang signifikan. Masalah gizi pada anak dapat menjadi faktor yang menghambat perkembangan fisik dan kognitif mereka. Masalah gizi disebabkan oleh berbagai faktor yang beragam, salah satunya pengetahuan ibu tentang gizi. Tujuan dari kegiatan ini adalah untuk meningkatkan pengetahuan, ibu guna mencegah masalah gizi pada balita, dengan merujuk pada sepuluh pedoman gizi seimbang. Metode pelaksanaan kegiatan ini yaitu penyuluhan yang diadakan di Kantor Hukum Tua Desa Wineru Kabupaten Minahasa Utara pada tanggal 28 Juli 2023. Sesi penyuluhan ini ditujukan khusus kepada ibu-ibu yang memiliki baita kerena secara umum di Indonesia, kelompok ini merupakan kelompok kunci untuk perawatan anak. Kegiatan diakhiri dengan Pemberian Makanan Tambahan (PMT) berupa biskuit dan susu kepada seluruh peserta yang hadir. Analisis data menggunakan uji-t berpasangan menunjukkan adanya perbedaan yang signifikan pada rata-rata kelompok sebelum dan setelah penyuluhan (p-value <0.05). oleh karena itu, dapat disimpulkan bahwa kegiatan penyuluhan ini berhasil dengan baik dalam meningkatkan pengetahuan, dan diharapkan bahwa peningkatan pengetahuan ini dapat diterapkan oleh peserta dalam praktik sehari-hari.